2018
DOI: 10.3390/su10051403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar on the Net Greenhouse Gas Emissions under Continuous Flooding and Water-Saving Irrigation Conditions in Paddy Soils

Abstract: In this study, we investigated the greenhouse gas emission under different application of biochar in the conditions of continuous flooding and water-saving irrigation in paddy fields, whereas, plant and soil carbon sequestration were considered in the calculation of net greenhouse gas emissions. The emission rates of methane (CH 4 ), carbon dioxide (CO 2 ), and nitrous oxide (N 2 O) gases were simultaneously monitored once every 7-10 days using the closed-chamber method. As a whole, the net greenhouse gas emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Annual CO 2 emission reported in the current study was generally consistent with previous studies, under different climate conditions and cropping systems (Abbas, Fares, Valenzuela, & Fares, 2012; Chi et al., 2020; Lentz et al., 2014; Qi, Niu, Zhou, Jia, & Gao, 2018). Nevertheless, our results were higher than those reported by Lentz et al.…”
Section: Discussionsupporting
confidence: 92%
“…Annual CO 2 emission reported in the current study was generally consistent with previous studies, under different climate conditions and cropping systems (Abbas, Fares, Valenzuela, & Fares, 2012; Chi et al., 2020; Lentz et al., 2014; Qi, Niu, Zhou, Jia, & Gao, 2018). Nevertheless, our results were higher than those reported by Lentz et al.…”
Section: Discussionsupporting
confidence: 92%
“…However, contrasting results are reported about the effect of AWD on N 2 O emission and grain yields even in paddy rice, one of the crops most suited for AWD. On the one hand, Lahue et al [ 97 ] found that AWD vs. FI curbed CH 4 emission by 80% in a clay-loamy soil, while significantly increasing the final yield; on the other hand, Lagomarsino et al [ 98 ] reported that AWD saved water by 70% and decreased CH 4 emission by 97%, but it increased N 2 O emission by five times in a clayey soil.…”
Section: Management Options To Mitigate N 2 O Emis...mentioning
confidence: 99%
“…plants and animal waste) under limited oxygen conditions [6][7][8]. Previous studies have shown that biochar application is a potential sustainable approach for saving irrigation water [9], removal of dimethyl sulfide [10], and soil carbon sequestration [11]. Owing to its large specific surface area, high density of negative surface charges, surface functional groups, adoption of biochar to remove or reduce organic, and inorganic contaminants from water/wastewater, including ammonium has been reported [8].…”
Section: Introductionmentioning
confidence: 99%